U-Value Analysis Of Coil in Box Heat Exchangers Using Log Mean Temperature Difference (LMTD) Method - Fitriyanti, Nurwulan (TURBO [Tulisan Riset Berbasis Online], 2024)
Heat exchangers take an important role in the vapor compression refrigeration system as either condenser or evaporator. In this study, the development of coil in box heat exchangers was conducted and analyzed as an evaporator. The device consisted of an insulated box with dimensions of 28 cm x 18 cm x 20 cm and the copper pipe with 0.006 m diameter and 3.65 m length. The heat was exchanged between the refrigerant R134a inside the pipe and the air outside the copper pipe. The temperatures at the inlets and outlets were measured by K-type thermocouples. Multiple experiments with the different air velocities were conducted. The log mean temperature difference (LMTD) method was used to analyze the overall heat transfer coefficient (U-Value) of the heat exchanger. The results show that the average U-Value was 76.9 W/(m2K).